2004
DOI: 10.1021/jf049737o
|View full text |Cite
|
Sign up to set email alerts
|

Phototransformation of Carboxin in Water. Toxicity of the Pesticide and Its Sulfoxide to Aquatic Organisms

Abstract: Sunlight exposure of aqueous suspensions of carboxin (1) causes its phototransformation to sulfoxide 2 and minor components. Similar effects are observed in the presence of humic acid or nitrate or at different pH values. Photoproducts 2-9 were isolated by chromatographic techniques and/or identified by spectroscopic means. Carboxin 1 and its main photoproduct sulfoxide 2 were tested to evaluate acute toxicity to primary consumers typical of the aquatic environment: the rotifer Brachionus calyciflorus and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Microorganisms and culture medium C. vulgaris and P. subcapitata were obtained from the Culture Collection of Algae and Protozoa (CCAP). The selection of these microorganisms was based on the following factors: (i) both microorganisms can be easily grown in laboratory cultures; (ii) different studies have shown that microorganisms from the genus Chlorella have been effectively applied in nutrients removal from wastewaters from different sources [31][32][33]; and (iii) P. subcapitata is a green microalga commonly used as a chemical toxicity bioassay organism [34,35] that has shown to be adapted to grow under different nitrogen and phosphorus concentrations [36]. Microalgae were inoculated in a modified standard medium [37] Table 1) were applied to mimic the compositions of real effluents, which present a wide variability.…”
Section: Methodsmentioning
confidence: 99%
“…Microorganisms and culture medium C. vulgaris and P. subcapitata were obtained from the Culture Collection of Algae and Protozoa (CCAP). The selection of these microorganisms was based on the following factors: (i) both microorganisms can be easily grown in laboratory cultures; (ii) different studies have shown that microorganisms from the genus Chlorella have been effectively applied in nutrients removal from wastewaters from different sources [31][32][33]; and (iii) P. subcapitata is a green microalga commonly used as a chemical toxicity bioassay organism [34,35] that has shown to be adapted to grow under different nitrogen and phosphorus concentrations [36]. Microalgae were inoculated in a modified standard medium [37] Table 1) were applied to mimic the compositions of real effluents, which present a wide variability.…”
Section: Methodsmentioning
confidence: 99%
“…As early as 1966, the launch of the fungicide carboxin started the research of succinate dehydrogenase inhibitor fungicides by pesticide workers. [ 9‐10 ] With the development of furametpyr in 1997, the mechanism of action of SDHIs has attracted widespread attention from researchers, [ 11 ] and many new SDHI fungicides have been developed, such as fluxapyroxad, [ 12 ] penflufen, [ 13 ] and isoflucypram (Figure 1). [ 13‐14 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…4,211) A sulfonic acid derivative as the major photoproduct of fipronil may imply that S-oxidation is a major pathway and the sulfone derivative is rapidly hydrolyzed; 212) however, the involvement of 211) and coumaphos, 126) and endoperoxide was a likely intermediate in the photolysis of fuberidazole. 4,213) In the case of thiabendazole, 2-carbamoyl, 2-carboxy, and 2-hydroxybenzimidazole were detected as the main products.…”
Section: Oxidationmentioning
confidence: 99%